HUBUNGAN ANTARA KUALITAS LAYANAN DAN PERSONAL SELLING DENGAN LOYALITAS NASABAH PT ASURANSI CAKRAWALA PROTEKSI CABANG BOGOR - Wijayanto, Arif; Moenis, Anoesyirwan; Muharam, Hari (Economicus, 2019)
The purpose of this study is to find out and analyze the relationship between service quality and Personal Selling together with customer loyalty to the Bogor Branch Protected Horizon Insurance. Data analysis uses multiple linear regression with data collection techniques through questionnaires. The results showed (1) there is a positive and significant relationship between service quality variables with customer loyalty with the value of the correlation coefficient (r) of 0.897, which means it is in the criteria of a very strong relationship. (2) There is a positive and significant relationship between the selling variables and customer loyalty with the value of the correlation coefficient (r) of 0.850, which means it is on the criteria of a strong relationship. (3) There is a positive and significant relationship between service quality and personal selling with customer loyalty together with the value of the correlation coefficient (r) of 0.902. It is known that the Adjusted R Square (R²) = 0.811 value, This shows that 81.1% customer loyalty is influenced by service quality and personal selling while the remaining 18.9%, customer loyalty is influenced by other factors that are not discussed in this study.